Theoretical aspects of professional competency of future teacher - Скалич, Люба Йосипівна (Pedagogy of Higher and Secondary Education, 2013)
Skalych L. J. Theoretical aspects of professional competency of future teacher. General approaches to the definition of contents «competency» and «competency building approach» on the modern level of development of education in Ukraine are presented in the article. The problems of teacher training to the realization of this approach while teaching are also analysed.